Polychloroprene Rubber/Reduced Graphene Oxide (RGO) Nanomembranes for Pervaporation Separation of Azeotropic Mixtures - G, Maya M.; George, Soney C.; Jose, Thomasukutty; Thomas, Sabu (Journal of Membrane and Separation Technology, 2014)
Chloroprene rubber is a high performance elastomer with remarkable ageing, heat and oil resistance. A new class of elastomeric nanocomposite was prepared by incorporating reduced graphene oxide (RGO) into chloroprene rubber (CR). RGO is synthesised from natural graphite, through GO route via Hummer’s method. This paper focuses on the influence of reduced graphene oxide on chloroprene rubber based elastomeric composites and their pervaporation separation of azeotropic liquid mixtures. The effect of concentration of RGO on separation factor, pervaporation separation index (PSI) and flux of the membranes were analysed. Chloroprene loaded with 0.9 phr (parts per hundred rubber) RGO shows an improved permeation rate among all other membranes while chloroform/acetone (80/20) azeotropic liquid mixture was used as feed solution. Flux increases with increasing the concentration of filler, reaches an optimum value and then decreases. Interestingly PSI also shows similar trend.